2017
DOI: 10.1371/journal.pcbi.1005571
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of multiscale stochastic biochemical reaction networks using exact moment derivation

Abstract: Biochemical reaction networks (BRNs) in a cell frequently consist of reactions with disparate timescales. The stochastic simulations of such multiscale BRNs are prohibitively slow due to high computational cost for the simulations of fast reactions. One way to resolve this problem uses the fact that fast species regulated by fast reactions quickly equilibrate to their stationary distribution while slow species are unlikely to be changed. Thus, on a slow timescale, fast species can be replaced by their quasi-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 84 publications
0
45
0
Order By: Relevance
“…Several studies recently have shown examples where using approximation QSSA can lead to considerable errors in the stochastic simulation [ 98 101 ]. Since then, a lot of effort has been done to find rigorous condition to check the validity of stochastic QSSA [ 99 , 100 ] or deriving an exact QSS of fast species rather than using approximate QSS [ 101 ]. Hence, depending the purpose of the study, one need to choose more carefully which simplification technique they should use.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies recently have shown examples where using approximation QSSA can lead to considerable errors in the stochastic simulation [ 98 101 ]. Since then, a lot of effort has been done to find rigorous condition to check the validity of stochastic QSSA [ 99 , 100 ] or deriving an exact QSS of fast species rather than using approximate QSS [ 101 ]. Hence, depending the purpose of the study, one need to choose more carefully which simplification technique they should use.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it follows that the region of attraction for the system (B34)-(B36) is given by R b1 ×R 3 where R b1 is the region of attraction of the equilibrium point z 0 γ 1 (x 0 , 0 . Thus, the assumptions of Tikhonov's theorem are satisfied and applying the theorem to the set of moment equations in (B1)-(B5) and (B9)-(B12) yields the result (19)- (25).…”
Section: Lemma 4 Consider the Full System Inmentioning
confidence: 96%
“…9,10 There have been several studies that obtain reduced-order representations of the CME under time-scale separation conditions. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Among these, a common approach used to reduce the complexity in the simulations of the CME is to approximate the fast variables by their deterministic quasi-steady state expressions. 19 However, validity of this method still remains under investigation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to improve the efficiency of SSA various methods have been developed exploiting the firing rate or the timescale separation of chemical reactions. Methods such as tau leaping, slow-scale SSA, stochastic quasi steady state approximation on enzyme catalyzed reactions are useful in this context with their own advantages and disadvantages (33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43) .…”
Section: Introductionmentioning
confidence: 99%